Anthropogenic changes to the nighttime environment. (7th April 2023) - Gaston, Kevin J; Gardner, Alexandra S; Cox, Daniel T C
Abstract: How the relative impacts of anthropogenic pressures on the natural environment vary between different taxonomic groups, habitats, and geographic regions is increasingly well established. By contrast, the times of day at which those pressures are most forcefully exerted or have greatest influence are not well understood. The impact on the nighttime environment bears particular scrutiny, given that for practical reasons (e.g., researchers themselves belong to a diurnal species), most studies on the impacts of anthropogenic pressures are conducted during the daytime on organisms that are predominantly day active or in ways that do not differentiate between daytime and nighttime. In the present article, we synthesize the current state of knowledge of impacts of anthropogenic pressures on the nighttime environment, highlighting key findings and examples. The evidence available suggests that the nighttime environment is under intense stress across increasing areas of the world, especially from nighttime pollution, climate change, and overexploitation of resources.